Cancer Stem Cell based molecular predictors of tumor recurrence in Oral squamous cell carcinoma - Mohanta, Simple; Sekhar Khora, Samanta; Suresh, Amritha (Archives of oral biology, 2019)
•Cancer stem cells are significant in prognosis given their role in resistance.•Meta-analysis identified head and neck cancer stem cell-specific markers (n = 221)•A subset of 54 genes correlated with recurrence in oral cancer cohort (n = 313).•A stem cell-specific panel (12) identified for prognostication in oral cancer.•Validation in patients identified CDK1 and NQO1 as significant prognosticators This study aimed to identify the cancer stem cell specific biomarkers that can be effective candidate prognosticators of oral squamous cell carcinoma. Microarray-based meta-analysis derived transcriptional profile of head and neck cancers was compared with the Cancer Stem Cell database to arrive at a subset of markers. This subset was further co-related with clinico-pathological parameters, recurrence and survival of oral cancer patients (n = 313) in The Cancer Genome Atlas database and in oral cancer (n = 28) patients. Meta-analysis in combination with database comparison identified a panel of 221 genes specific to head and neck cancers. Correlation of expression levels of these markers in the oral cancer cohort of The Cancer Genome Atlas (n = 313) with treatment outcome identified 54 genes (p < 0.05 or fold change >2) associated with disease recurrence, 8 genes (NQO1, UBE2C, EDNRB, FKBP4, STAT3, HOXA1, RIT1, AURKA) being significant with high fold change. Assessment of the efficacy of the subset (n = 54) as survival predictors identified an additional 4 genes (CDK1, GINS2, PHF5 A, ERBB2) that co-related with poor disease-free survival (p < 0.05). CDK1 showed a significant association with the clinical stage, margin status and with advanced pathological parameters. Initial patient validation indicated that CDK1 and NQO1 significantly co-related with the poor disease-free and overall survival (p < 0.05). This panel of oral cancer specific, cancer stem cell associated markers identified in this study, a subset of which was validated, will be of clinical benefit subject to large scale validation studies.